Quantifying the potential value of entomological data collection for programmatic decision-making on malaria control in sub-Saharan African settings - Nora Schmit; Hillary M. Topazian; Matteo Pianella; Giovanni D. Charles; Peter Winskill; Penelope A. Hancock; Ellie Sherrard-Smith; Katharina Hauck; Thomas S. Churcher; Azra C. Ghani (Malaria Journal)
Abstract Background The availability of many tools for malaria control leads to complex decisions regarding the most cost-effective intervention package based on local epidemiology. Mosquito characteristics influence the impact of vector control, but entomological surveillance is often limited due to a lack of resources in national malaria programmes. Methods This study quantified the monetary value of information provided by entomological data collection for programmatic decision-making using a mathematical model of Plasmodium falciparum transmission. The 3-year impact and cost of various intervention packages was simulated in different sub-Saharan African settings, including combinations of scaling-up insecticide-treated nets (ITN), switching to next-generation ITNs, and a treatment and prevention package. The DALYs averted and their net monetary benefit were compared at different cost-effectiveness thresholds and the value of resolving uncertainty in entomological model parameters was calculated. Results Across transmission settings and at cost-effectiveness thresholds over US$170 per DALY averted, the most cost-effective intervention package was switching to and scaling up pyrethroid-pyrrole ITNs combined with the treatment and prevention package. The median expected value of perfect information on the entomological indicators was US$0.05 (range 0.02–0.23) and US$0.17 (range 0.09–1.43) per person at risk at thresholds of US$75 and US$1000 per DALY averted, respectively. This represented less than 2% of the net monetary benefit of implementing the most cost-effective intervention package. Value of information estimates at cost-effectiveness thresholds over US$250 were higher than current investments into entomological monitoring by the US President’s Malaria Initiative. Conclusions These results suggest that entomological data collection should not delay implementation of interventions with demonstrated efficacy in most settings, but that sustained investments into and use of entomological surveillance are nevertheless worthwhile and have broad value to national malaria programmes.